Bladder preservation therapy for muscle invasive bladder cancer: the past, present and future. (7th September 2020) - Kimura, Tomokazu; Ishikawa, Hitoshi; Kojima, Takahiro; Kandori, Shuya; Kawahara, Takashi; Sekino, Yuta; Sakurai, Hideyuki; Nishiyama, Hiroyuki
Abstract: Radical cystectomy is the gold standard treatment for muscle invasive bladder cancer, but some patients have medically inoperable disease or refuse cystectomy to preserve their bladder function. Bladder preservation therapy with transurethral resection of the bladder tumor and concurrent chemoradiotherapy, known as trimodal treatment, is regarded to be a curative-intent alternative to radical cystectomy for patients with muscle invasive bladder cancer during the past decade. After the development of immune checkpoint inhibitors, a world-changing breakthrough occurred in the field of metastatic urothelial carcinoma and many clinical trials have been conducted against non-muscle invasive bladder cancer. Interestingly, preclinical and clinical studies against other malignancies have shown that immune checkpoint inhibitors interact with the radiation-induced immune reaction. As half of the patients with muscle invasive bladder cancer are elderly, and some have renal dysfunction, not only as comorbidity but also because of hydronephrosis caused by their tumors, immune checkpoint inhibitors are expected to become part of a new therapeutic approach for combination treatment with radiotherapy. Accordingly, clinical trials testing immune checkpoint inhibitors have been initiated to preserve bladder for muscle invasive bladder cancer patients using radiation and immune checkpoint inhibitors with/without chemotherapy. The objective of this review is to summarize the evidence of trimodal therapy for muscle invasive bladder cancer during the past decade and to discuss the future directions of bladder preservation therapy in immuno-oncology era. Abstract : This review article summarized the evidence and on-going clinical trials of bladder preservation therapy for muscle invasive bladder cancer in the past and future immuno-oncology era.